Embedding genetics experiments in restoration to guide plant choice for a degraded landscape with a changing climate. (30th December 2021) - Bailey, Tanya G.; Harrison, Peter A.; Davidson, Neil J.; Weller‐Wong, Akira; Tilyard, Paul; Steane, Dorothy A.; Vaillancourt, René E.; Potts, Brad M.
Summary: We overview an array of common garden genetics trials established across multiple sites and embedded in restoration plantings in the harsh, modified Midlands region of the island of Tasmania, Australia. The steps in establishing the common gardens, the diversity of experimental designs employed and their objectives are described. These trials provide a long‐term framework to test species choices and provenancing strategies, as well as enhance our understanding of adaptive genetic variation within key eucalypt species used for ecological restoration. Early results signal genetic‐based differences in early‐age performance, and we showcase the multiple benefits of integrating research infrastructure into restoration plantings.